Device-related complications in transvenous versus subcutaneous defibrillator therapy during long-term follow-up: the PRAETORIAN-XL trial - Olde Nordkamp, Louise R.A; de Veld, Jolien A.; Ghani, Abdul; Kuschyk, Jürgen; Bonnemeier, Hendrik; Bode, Kerstin; Boersma, Lucas V.A.; de Weger, Anouk; de Jong, Jonas S.S.G.; Jansen, Ward P.J.; Alings, Marco; Bijsterveld, Nick; et al. (Circulation, 2025)
BACKGROUND: - The PRAETORIAN trial (A Prospective, Randomized Comparison of Subcutaneous and Transvenous Implantable Cardioverter Defibrillator Therapy) investigated the efficacy and safety of the subcutaneous implantable cardioverter defibrillator (S-ICD) compared with a transvenous ICD (TV-ICD) and showed noninferiority of the S-ICD with regard to the composite end point of device-related complications and inappropriate shocks after 49.1 months. Complications associated with transvenous leads are expected to occur after longer follow-up. The PRAETORIAN-XL trial aims to investigate whether the S-ICD is superior to the TV-ICD with respect to device-related complications at 8-year follow-up. - METHODS: - The PRAETORIAN trial randomized patients with a class I or IIa indication for ICD therapy without the need for pacing to either S-ICD or TV-ICD among 39 centers in the United States and Europe between March 2011 and January 2017. The follow-up was extended after 49.1 months by an additional 4 years for the PRAETORIAN-XL trial. The primary end point was the composite of all device-related complications. Complications could be related or unrelated to the lead and minor or major, with major complications being those requiring an invasive intervention. End points were analyzed according to the modified intention-to-treat principle using a Fine-Gray subdistribution hazards model to account for competing risks. An as-treated analysis was performed using a Cox proportional hazards model with device type as time-dependent variable. - RESULTS: - Patients were randomized to S-ICD (n=426) and TV-ICD (n=423). Twenty-one percent of the S-ICD group versus 18% of the TV-ICD group were women. The median age at implantation was 63 (interquartile range, 54-69) years for the S-ICD and 64 (interquartile range, 56-69) years for the TV-ICD. After a median follow-up of 87.5 months, all device-related complications (major and minor combined) were not significantly different in the modified intention-to-treat analysis (subdistribution hazard ratio, 0.73 [95% CI, 0.48-1.12]); P=0.15). However, TV-ICD patients more often had a major complication or lead-related complication (P=0.03 and P<0.001, respectively). Moreover, the as-treated analysis showed significantly more complications in patients with a TV-ICD compared with an S-ICD (hazard ratio, 0.64 [95% CI, 0.41-0.99]; P=0.047). - CONCLUSIONS: - The PRAETORIAN-XL trial demonstrated that there was no significant difference between the S-ICD and TV-ICD in all device-related complications during long-term follow-up. However, the TV-ICD carries a higher risk of major and lead-related complications compared with S-ICD therapy. The S-ICD should therefore be considered for all patients without a pacing indication who are evaluated for ICD therapy. - REGISTRATION: - URL: https://www.clinicaltrials.gov; Unique identifier: NCT01296022.
Online veröffentlicht: 25. April 2025
Gesehen am 16.09.2025